(untitled) (Scottish Archaeological Internet Reports, 2009)
The excavation at Dunasbroc has provided a tantalising glimpse into a site, re-used over time with, as yet, no excavated parallels elsewhere in Britain. This relatively small site has raised more questions than it has answered, but has also confirmed the thesis that coastal stack and promontory sites have a much longer and more diverse history than has previously been thought.